2008
DOI: 10.3382/ps.2007-00393
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Salmonella Enteritidis in Shell Eggs Using Directional Microwave Technology

Abstract: Microwaves have been shown to cause thermal as well as nonthermal destruction of pathogens such as Salmonella Enteritidis, which is commonly found in shell eggs. The objective of this study was to examine the use of new directional microwave technology to reduce Salmonella Enteritidis without causing any detrimental effects on quality in white and brown eggs. Treatments were control and microwaved white and brown eggs. Applying directional microwave technology resulted in a 2-log reduction of Salmonella Enteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Different studies have been proposed about the use of microwave to reduce bacterial load in shell eggs (Jeng et al 1987;Stadelman et al 1996;Ferroni et al 2003;Dev et al 2007;Sivaramakrishnan 2007;Lakins et al 2008).…”
Section: Microwave Pasteurizationmentioning
confidence: 98%
See 3 more Smart Citations
“…Different studies have been proposed about the use of microwave to reduce bacterial load in shell eggs (Jeng et al 1987;Stadelman et al 1996;Ferroni et al 2003;Dev et al 2007;Sivaramakrishnan 2007;Lakins et al 2008).…”
Section: Microwave Pasteurizationmentioning
confidence: 98%
“…As regards directional microwave technology, Lakins et al (2008) andFerroni et al (2003) proposed treating eggs by an innovative technology very different from commercial or household microwaves using microwave equipment with horizontal and rotary movement and several sources of (2003) reported a reduction of up to 80% in Salmonella Enteritidis using a 10 3 cfu/ml yolk inoculum level. The authors reported that the pH, the weight and the sensory characteristics showed no significant differences between eggs treated by directional microwave technology and non-treated eggs.…”
Section: Microwave Pasteurizationmentioning
confidence: 98%
See 2 more Smart Citations
“…Kuo et al (1997) determined that UV radiation significantly reduced S. typhimurium inoculated on shell eggs. Directional microwave technology resulted in more than 2-log reduction of S. enteritidis in shell eggs without causing any detrimental effects to quality reviewed by Lakins et al (2008). The effectiveness of steam treatments on meat and poultry has been investigated, which the presence of a number of pathogens may be reduced by the application of steam to meat surfaces, mostly gram negative enteric pathogens, such as Escherichia coli O157:H7 and a number of Salmonella serotypes (James et al, 2000;Phebus et al, 1997;Whyte et al, 2003).…”
Section: Control Of Salmonella In Foodsmentioning
confidence: 99%